COLOR BLIND PREVALENCE OF ELEMENTARY STUDENT IN SUMBERSARI SUBDISTRICT, JEMBER - Rike Oktarianti; Lutfia Azizah; Eva Tyas Utami (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2022)
Red-green color blindness is the most common type of color blindness. Color blindness disorders occur due to genetic factors determined by the recessive gene c (color blind) which is linked to the X chromosome. This study aims to determine the prevalence and frequency of color blind alleles and to determine the pattern of inheritance of color blind genes by conducting pedigree analysis on color blindness student’s family. The research was conducted in 13 public elementary schools, Sumbersari subdistrict, Jember Regency with a multistage cluster sampling method of sampling with a total sample of 286. Detection of color blindness using Ishihara's methods. Based on the results of this study, the color blindness prevalence of elementary school students in Sumbersari subdistrict, Jember was 2.79% with the prevalence in males and female were respectively as 4.86% and 0.7%. The allele frequency of color blindness was 0.021 and the normal allele frequency was 0.979. The pedigree analysis of a color blind student family shows the gene of color blindness is inherited in a criss-cross inheritance pattern.